Rhamnolipids and fengycins, very promising amphiphilic antifungal compounds from bacteria secretomes, act on Sclerotiniaceae fungi through different mechanisms - Botcazon, Camille; Bergia, Thomas; Lecouturier, Didier; Dupuis, Chloé; Rochex, Alice; Acket, Sébastien; Nicot, Philippe; Leclère, Valérie; Sarazin, Catherine; Rippa, Sonia (Frontiers in Microbiology, 2022)
Rhamnolipids (RLs) and fengycins (FGs) are amphiphilic lipid compounds from bacteria secretomes proposed to replace synthetic pesticides for crop protection. They both display plant defense triggering properties and direct antimicrobial activities. In particular, they have well reported antifungal effects against phytopathogenic fungi. RLs and FGs are considered to act through a direct interaction with membrane lipids and a destabilization of microorganism plasma membrane, thereby limiting the risk of resistance emergence. The main objective of this work was to gain insights in the antimycelial mode of action of these metabolites to promote them as environment and human health friendly biocontrol solutions. Their biocidal effects were studied on two Sclerotiniaceae fungi responsible for diseases in numerous plant species worldwide. We show here that different strains of Botrytis cinerea and Sclerotinia sclerotiorum have opposite sensitivities to RLs and FGs on plate experiments. Overall, B. cinerea is more sensitive to FGs while S. sclerotiorum is more sensitive to RLs. Electron microscopy observations demonstrated that RLs induce mycelial destructuring by asperities emergence and hyphal fusions whereas FGs promote swelling and formation of vesicle-like structures due to vacuole fusions and autophagy. Permeability studies, phosphatidylserine externalization and reactive oxygen species production assessments showed a programmed cell death triggering by RLs at medium concentrations (until 50 µg mL-1) and necrosis characteristics at higher concentration. Programmed cell death was always observed on hyphae treated with FGs. Quantifications of mycelial ergosterol content indicated that a higher ergosterol rate in S. sclerotiorum correlates with increasing sensitivity to RLs. Oppositely, a lower ergosterol rate in B. cinerea correlates with increasing sensitivity to FGs, which was confirmed by ergosterol biosynthesis inhibition with tebuconazole. This gain of knowledge will help to better understand the mode of action of RLs and FGs to fight specific plant fungal diseases.